FINANCING INSTRUMENTS OF GREEN ECONOMY AND RELEVANCE OF GREEN FINANCING IN UZBEKISTAN - Matkarimov Ulug’bek; Shodiyev Erkin Temirovich (Journal of new century innovations, 2024)
Abstract: The article examines the importance of green accounting standards in economic growth. In particular, main tools and instruments to achieve green economy are discussed in this article.